If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3x + -12 = 180 Reorder the terms: -12 + X + 3x = 180 Solving -12 + X + 3x = 180 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '12' to each side of the equation. -12 + X + 12 + 3x = 180 + 12 Reorder the terms: -12 + 12 + X + 3x = 180 + 12 Combine like terms: -12 + 12 = 0 0 + X + 3x = 180 + 12 X + 3x = 180 + 12 Combine like terms: 180 + 12 = 192 X + 3x = 192 Add '-3x' to each side of the equation. X + 3x + -3x = 192 + -3x Combine like terms: 3x + -3x = 0 X + 0 = 192 + -3x X = 192 + -3x Simplifying X = 192 + -3x
| 7=2t-5 | | X(3x-12)=180 | | 4x+(5+2x)=2 | | 5x+18-4=-36 | | x^2+6-30=0 | | 2r-45-19r=-53+r | | w-6=-48 | | y=4+(-2) | | -10-6x+4x=3-4x-1 | | 2x+y=39.50 | | w-6=48 | | y=8-3/4(-1) | | 4=6(x-2)-8x | | .5(3x+6)=1.1-(x+2) | | y=8-3/4(1) | | 15x-8y=138 | | y=8-3/4(0) | | 7(y-8)+24=-27(y-6) | | -5p=-8p+3p | | -2x-(4+x)=2 | | n=-70 | | (5x+10)+(6x)=180 | | -6(x-8)=-54 | | -9(c+1)=5 | | 3.(x-2)=2x-4 | | 3a-24= | | 7y-32=-27y-6 | | 43-(3x+9)=3(x+2)+x | | 2.89+a=17.10 | | -2x-(4x)=2 | | 3-n=-n-1+4 | | .5x+.33x-.2(x+3)=.1 |